Implementation of the scientific approach in the Merdeka curriculum at the high school level - Diyas Fathulloh; Muhammad Arifin Rahmanto (Edumaspul: Jurnal Pendidikan, 2024)
This research was conducted to explore the application of scientific approaches in the Merdeka Curriculum with a focus on its impact on educational outcomes in Indonesia. The methodology used in this study is descriptive qualitative, by utilizing literature research to collect relevant data. Analysis is carried out by setting goals, clarifying important concepts, defining units of analysis, collecting relevant data, and establishing conceptual relationships between data. The results showed that a scientific approach, which involves observation, questioning, information gathering, reasoning, and communication, can improve students' intellectual and critical thinking abilities. The flexibility of the Independent Curriculum and the emphasis on student-centered learning support the active involvement and independence of learners. This approach is in keeping with the demands of modern education, which aims to prepare students for challenges in an ever-evolving global landscape.